Accuracy of physician assessment of treatment preferences and health status in elderly patients with higher-risk myelodysplastic syndromes. Issue 8 (August 2015) - Caocci, G.; Voso, M.T.; Angelucci, E.; Stauder, R.; Cottone, F.; Abel, G.; Nguyen, K.; Platzbecker, U.; Beyne-Rauzy, O.; Gaidano, G.; Invernizzi, R.; Molica, S.; et al.
Highlights It is essential for physicians to focus attention on patient needs and preferences. Physicians' perceptions are frequently inconsistent with MDS patients' preferences. Physicians are poor judges of health status of their higher risk MDS patients. Decision aid-tools in the setting of higher-risk MDS might be helpful.